Проблеми екологічного страхування в Україні - Якимчук, С.А. (Культура народов Причерноморья, 2013)
Розглянуто поняття екологічного страхування, його мету, об’єкт та суб’єкт страхування.
Визначено основні функції екологічного страхування. Досліджено проблеми, які існують при формуванні
екологічного страхування в Україні. Запропоновано шляхи удосконалення системи екологічного
страхування.
Система страхування екологічних ризиків в Україні перебуває на стадії формування. Основними
проблемами впровадження екологічного страхування є: законодавча неврегульованість екологічного
страхування; низька фінансова спроможність підприємств; труднощі в оцінці екологічних ризиків
тощо. Рассмотрены понятия экологического страхования, его цели, объект и субъект
страхования. Определены основные функции экологического страхования. Исследованы проблемы,
которые существуют при формировании экологического страхования в Украине. Предложены пути
совершенствования системы экологического страхования.
Система страхования экологических рисков в Украине находится на стадии формирования. Основными
проблемами внедрения экологического страхования являются: законодательная неурегулированность
экологического страхования; низкая финансовая состоятельность предприятий; трудности в оценке
экологических рисков и т.д. The aim of the article is to analyze the concept of environmental insurance, research problems in this
area and their solutions for improving environmental management in Ukraine.
The paper considers different approaches to the interpretation of environmental insurance. Defined purpose,
object and subject of environmental insurance. Also, the basic functions ekostrahuvannya.
The problems that exist in the implementation of environmental insurance in Ukraine. Analysis of the legal
framework in the field of environmental insurance. Definitely form ekostrahuvannya. The most acceptable form
is mandatory ekostrahuvannya.
Environmental security - especially the most complex type of insurance that is specific (the relationship of legal
mechanism, involving experts in ecology for environmental audits of insurers).
Environmental risks insurance system in Ukraine is under development and requires the development of effective
mechanisms for its formation. The main problems of implementation of environmental insurance in Ukraine are:
lack of legislation establishing mandatory environmental insurance, low financial capacity of enterprises, lack of
environmental auditing practices, difficulties in assessing environmental risks, the lack of statistics on man-made
disaster that can not adequately assess the damage and risks of their occurrence, the virtual absence of
interaction between government agencies, academic and commercial institutions, enterprises and organizations.